Physico-chemical characteristics of textile effluent collected from Erode, Pallipalayam and Bhavani polluted regions, Tamilnadu, India - Sathiyaraj, Ganesan; Chellappan Ravindran, K.; Hussain Malik, Zakir (Journal of Ecobiotechnology, 2017)
Present study perceives that textile dye effluents of Erode, Pallipalayam and Bhavani region have substantial volume of EC, pH, TDS, COD, BOD, Sodium Chloride, Calcium, Magnesium, Potassium and heavy metals. Results point out that irrespective of the source, effluent properties exceeded permissible limits by WHO/ FAO/Federal Environmental Protection Agency for irrigation. The textile industry consumes a mixture of chemicals and huge amount of water during the production process. About 200 L of water are used to produce 1 kg of textile. The textile effluent can cause several health infections like haemorrhage, ulceration of skin, nausea, skin irritation and dermatitis.